The Role of Bentonite Clay on Improvement in Char Adhesion of Intumescent Fire-Retardant Coating with Steel Substrate - Kaur, J. (Springer Verlag, 2017)
The adhesion of char with the substrate is important in improving the fire protection of substrate. This study presents the effects of bentonite clay on intumescent fire-retardant coating for improving the adhesion of char with steel substrate, thermal performance and residual weight of intumescent fire-retardant coatings. A range of expandable graphite-based intumescent coating formulations were developed using a shear mixer with various additives. In a selected formulation, bentonite clay additive was incorporated to investigate the improvement in adhesion of coating and char with steel substrate. The substrate was sandblasted and coated with a primer coating of zinc phosphate followed by intumescent coating. Char expansion and fire performance were measured by furnace fire test and Bunsen burner test. Residual weight was determined by thermogravimetric analysis, and char detachment was measured by scanning electron microscopy. The bonding shear strength was measured according to ASTM 3163. Results showed improvement in residual weight to 33.45 wt. The substrate temperature was reduced to 170 ∘C , and char separation was reduced to 130 μ m. Shear strength was improved to 9.90 MPa for an intumescent coating formulation containing 6 wt of bentonite clay and 1.75 MPa for formulation without bentonite clay. © 2017, King Fahd University of Petroleum & Minerals.